2019
DOI: 10.3928/01484834-20191021-08
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Collaboration in Undergraduate Nursing Students

Abstract: Background: The role of the nurse educator is to prepare students to collaborate and practice competently and safely. One way of promoting collaboration is with the use of students as standardized patients (SPs). Method: This exercise used undergraduate nursing students in collaboration with graduate nurse practitioner (NP) students in an advanced health assessment course. Undergraduate students were assigned a specific disease process to review, then a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Students' experience of collaborative study such as clinical training and group assignments in the curriculum is thought to have positive effects on building collaborative ability. Problembased learning [36] and standardized patient (SP) education strategies [19] that use students to improve collaboration and collaborative testing improve academic achievement [16], therefore a variety of collaboration strategies are needed for nursing education. In addition, collaboration across professions has become equally important as collaboration within the nursing profession for providing the best results for patients [37], and it will be necessary to introduce cross-professional education into the nursing curriculum and study its effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Students' experience of collaborative study such as clinical training and group assignments in the curriculum is thought to have positive effects on building collaborative ability. Problembased learning [36] and standardized patient (SP) education strategies [19] that use students to improve collaboration and collaborative testing improve academic achievement [16], therefore a variety of collaboration strategies are needed for nursing education. In addition, collaboration across professions has become equally important as collaboration within the nursing profession for providing the best results for patients [37], and it will be necessary to introduce cross-professional education into the nursing curriculum and study its effects.…”
Section: Discussionmentioning
confidence: 99%
“…Existing research on SEC among nursing students has explored partial correlations between some elements of SEC skills such as critical thinking [8,9], problem-solving [10], creativity [18], emotional intelligence [12][13][14][15], collaboration [19], and self-directed learning [8,10,18]. However, limited research has sought to analyze correlations between SEC and AA among nursing students in a comprehensive manner, as well as the relative importance of core SEC skills and correlations between the application of those core skills and academic performance.…”
Section: Introductionmentioning
confidence: 99%
“…Although leadership behaviors improve from service-learning in a leadership course, this study further demonstrates behaviors can be learned from an interactive online module. Prior research has shown that the use of standardized patients as a pedagogical approach promotes nursing collaboration as the reflective learning process facilitates critical thinking and communication (Nielson et al, 2019). Similarly, the process of applying content to video-based scenarios utilized in the COMFORT module revealed that students can recognize when to apply new communication behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, it presented that the nursing undergraduate institutions should have at least one of the tertiary comprehensive affiliated hospitals, total number of beds should meet the needs of students in internships process. Since community nursing is an important aspect of adaptation required for future development of nursing discipline, it is recommended that the schools should establish the relationships with the urban community health service centers and the rural hospitals or the township health centers [13,14] . It should also have stable mental health centers or psychiatric as the practice or teaching bases to ensure the completion of students’ study task, which expected to promote the integrated development of clinical nursing teaching in practice bases.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al Medicine (2021) 100:20 Medicine establish the relationships with the urban community health service centers and the rural hospitals or the township health centers. [13,14] It should also have stable mental health centers or psychiatric as the practice or teaching bases to ensure the completion of students' study task, which expected to promote the integrated development of clinical nursing teaching in practice bases.…”
Section: 1%mentioning
confidence: 99%